The Effect of Ethical Leadership on Organizational Citizenship Behavior and Turnover Intention with Intrinsic Motivation as a Mediating Variable A Study of Companies in the Trade and Services Sector - Febriansyah; Darmaputri Savitri, Aulia; Vathia Khairunnisa, Elfira; Andriyani, (International Journal of Scientific Research and Management (IJSRM), 2023)
This research aimed to investigate the influence of Ethical Leadership on Intrinsic Motivation, the influence of Ethical Leadership on Turnover Intention, the influence of Ethical Leadership on Organizational Citizenship Behavior, the impact of Intrinsic Motivation as a mediating variable on Turnover Intention, and the effect of Intrinsic Motivation as a mediating variable on Organizational Citizenship Behavior. Primary data for this study were collected directly through the completion of questionnaires from 243 employees. The data analysis method employed in this research was Partial Least Squares (PLS). The results indicate a strong connection between ethical leadership and both intrinsic motivation and organizational citizenship behavior, emphasizing the importance of ethical leadership practices within organizations. These practices, including ethical leadership training, fostering an organizational culture that encourages ethics, and applying ethical principles in decision-making, can significantly enhance intrinsic motivation and workplace behavior. Conversely, the study reveals that ethical leadership does not significantly influence turnover intention, suggesting that organizations should consider other factors affecting employees' intentions to leave their jobs, such as the work environment, career development, and work-life balance. While intrinsic motivation, when examined independently, may not directly impact organizational citizenship behavior, it plays a pivotal moderating role in influencing workplace behavior. Organizations are encouraged to explore additional factors that more directly shape organizational citizenship behavior, acknowledging the crucial role of intrinsic motivation in moderating these relationships